Lean Software Development--Building and Shipping Two Versions. - MATSUDAIRA, KATE (Communications of the ACM, 2015)
The article presents a model of lean software development which focuses on differentiating the methods of designing the prototype and second version of a given project. The author highlights how prototypes and subsequent versions are fundamentally approached differently, how different computer programmers are more aligned to either one of the design phases, and how this v1/v2 process minimizes over-engineering.